2017
DOI: 10.1159/000477422
|View full text |Cite
|
Sign up to set email alerts
|

Routine Monitoring of Sodium and Phosphorus Removal in Peritoneal Dialysis (PD) Patients Treated with Continuous Ambulatory PD (CAPD), Automated PD (APD) or Combined CAPD+APD

Abstract: Background: Adequate removal of sodium (Na) and phosphorus (P) is of paramount importance for patients with dialysis-dependent kidney disease can easily quantified in peritoneal dialysis (PD) patients. Some studies suggest that automated PD (APD) results in lower Na and P removal. Methods: In this study we retrospectively analysed our data on Na and P removal in PD patients after implementation of a routine monitoring in 2011. Patients were stratified in those treated with continuous ambulatory PD (CAPD, n=24)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 20 publications
2
8
1
Order By: Relevance
“…Peritoneal sodium removal was also associated with the volume of icodextrin prescribed, supporting other studies which have shown that volume status is better maintained with icodextrin compare to 22.7 g/L glucose exchanges [26]. Whereas some smaller earlier studies did not demonstrate an effect of hypertonic glucose dialysates and peritoneal sodium losses [9], we noted a univariate association, which would be expected as hypertonic dialysates would be expected to increase ultrafiltration [10, 24]. There was a weak association between higher mean arterial blood pressure and lower peritoneal sodium losses, and previous studies have either reported a similar association or no effect of peritoneal sodium losses on blood pressure [9, 27].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Peritoneal sodium removal was also associated with the volume of icodextrin prescribed, supporting other studies which have shown that volume status is better maintained with icodextrin compare to 22.7 g/L glucose exchanges [26]. Whereas some smaller earlier studies did not demonstrate an effect of hypertonic glucose dialysates and peritoneal sodium losses [9], we noted a univariate association, which would be expected as hypertonic dialysates would be expected to increase ultrafiltration [10, 24]. There was a weak association between higher mean arterial blood pressure and lower peritoneal sodium losses, and previous studies have either reported a similar association or no effect of peritoneal sodium losses on blood pressure [9, 27].…”
Section: Discussionsupporting
confidence: 86%
“…These patients had greater residual renal function and urinary sodium losses, thus over-all losses were similar between modalities, supporting the results of smaller studies [10, 24]. As with many centres we practice incremental dialysis, with peritoneal dialysis prescriptions taking into account residual renal function [25], and as such patients with greater residual renal function and urinary sodium losses had correspondingly lower peritoneal sodium losses.…”
Section: Discussionmentioning
confidence: 63%
“…The authors also showed equal sodium removal in both modalities [ 62 ]. Similarly, a more recent publication reported that sodium removal was not associated with PD modality but increased with the use of icodextrin and with solutions of higher glucose concentration [ 63 ]. Based on the above, it seems that given the appropriate adjustment of the prescribed dialysis dose in the case of RRF reduction and the liberal use of icodextrin, APD can be successfully implemented in achieving ultrafiltration goals and euvolemia [ 64 , 65 ].…”
Section: Residual Renal Function–blood Pressure–ultrafiltration–sodiumentioning
confidence: 99%
“…Removal of excess phosphate is of crucial importance for the health of all end-stage renal disease (ESRD) patients. In the aforementioned study by Moor and coworkers, a higher phosphate removal was dependent only on increased dialysate volume [ 63 ]. In a retrospective study of 380 patients, higher phosphate peritoneal removal was associated with the use of CAPD and fast transport status.…”
Section: Phosphate Removalmentioning
confidence: 99%
“…Continuous ambulatory PD (CAPD) is generally believed to result in higher SR than automated PD (APD) by virtue of typically having less frequent and longer cycles (and hence less sodium sieving) [16]. However, some authors have suggested that both modalities could result in similar sodium elimination with optimal PD prescription [17, 18]. In a study on 158 prevalent PD patients, Davison et al[19] reported no difference between APD and CAPD with regard to the ratio of extracellular fluid volume to total body water using bioimpedance spectroscopy.…”
Section: Pd Modalitiesmentioning
confidence: 99%